2018
DOI: 10.3389/fpsyt.2018.00597
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Association Between Genetic Variants in Circadian Rhythm Genes and Posttraumatic Stress Symptoms Identifies a Potential Functional Allele in the Transcription Factor TEF

Abstract: Previous studies suggest that genetic variants within genes affecting the circadian rhythm influence the development of posttraumatic stress symptoms (PTSS). In the present study, we used data from three emergency care-based cohorts to search genetic variants in circadian pathway genes previously associated with neuropsychiatric disorders for variants that influence PTSS severity. The three cohorts used included a discovery cohort of African American men and women enrolled following motor vehicle collision (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…Also in the absence of non-traditional work patterns, nighttime trauma exposure may be specifically associated with acutely disturbed circadian rhythmicity and sleep. Circadian dysregulation is increasingly recognized as biological correlate of PTSD ( Dayan et al, 2016 ), and genetic variation in circadian rhythm are related to PTSD risk ( Linnstaedt et al, 2018 ). Additionally, pre-trauma blunted ultradian corticosterone patterns were found to be a vulnerability factor for PTSD-like behavior in rodents ( Danan et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also in the absence of non-traditional work patterns, nighttime trauma exposure may be specifically associated with acutely disturbed circadian rhythmicity and sleep. Circadian dysregulation is increasingly recognized as biological correlate of PTSD ( Dayan et al, 2016 ), and genetic variation in circadian rhythm are related to PTSD risk ( Linnstaedt et al, 2018 ). Additionally, pre-trauma blunted ultradian corticosterone patterns were found to be a vulnerability factor for PTSD-like behavior in rodents ( Danan et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the enrichment of genes associated with circadian rhythms was expected given the 20 wealth of PTSD research in this area, and the common presentation of PTSD with sleep dysfunction, including insomnia and nightmares. To name a few, studies revealed altered circadian rhythms of cortisol in individuals with PTSD (Yehuda et al, 1996), and association between PTSD and variants in circadian rhythm genes (Linnstaedt et al, 2018;Logue et al, 2013). Finally, the enrichment of the PSD-95 gene set aligns with substantial evidence 25 supporting a role for PSD-95 in synapse-related dysfunction in several neuropsychiatric disorders (Penzes et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…RORA is involved in the REV-ERB loop that influences the molecular clock and has been identified as PTSD risk gene [ 220 , 221 ]. Another gene loop involved in the molecular clock, a PARb-ZIP factor, TEF (variant rs5758324), showed strong associations with PTSD symptoms [ 222 ]. These findings further emphasize wide reaching implications involved in circadian disruption.…”
Section: Circadian Rhythms and Bbb-associated Neurological Disordersmentioning
confidence: 99%